Multiplex Tests for Respiratory Tract Infections: The Direct Utility of the FilmArray Respiratory Panel in Emergency Department - Siyuan Yang; Hui Li; Yunxia Tang; Fengting Yu; Chengjie Ma; Huimin Zhang; Lin Pang; Hongxin Zhao; Linghang Wang (Canadian Respiratory Journal)
Background. The FilmArray Respiratory Panel with multiplex targets for respiratory pathogens has been widely used and verified in clinical trials in special test settings. However, it is necessary to evaluate the panel’s performance at the point of care directly, in nonspecific test settings. Methods. Patients with respiratory tract infections were enrolled from among emergency department visitors, and all steps, including the collection of specimens and testing, were performed by our clinicians. Results. Among 270 patients, 196 (72.6%) patients were found to have one or more pathogens. For signal pathogen detection, influenza A virus had the highest rate of detection; 45 (16.7%) of the patients had two or more respiratory pathogens codetected, and most of the multiplex pathogens were rhinovirus/enterovirus codetected with Bordetella pertussis (17.8%). The information provided by the FilmArray had an impact on the prescription of antimicrobials, and there were differences in the rates of antibiotic prescriptions and anti-influenza prescriptions among patients. Conclusions. Use of the FilmArray by clinical staff was successfully implemented in the emergency department for the first time in China. The FilmArray has the potential for point-of-care testing in nonspecific settings.